The effects of exercise, heat, cooling and rehydration strategies on cognitive function in football players - Bandelow, S.; Maughan, R.; Shirreffs, S.; Ozgünen, K.; Kurdak, S.; Ersöz, G.; Binnet, M.; Dvorak, J. (Scandinavian Journal of Medicine & Science in Sports, 2010)
We investigated the cognitive effects of exercising in the heat on the field players of two football teams in a series of three matches. Different rehydration and cooling strategies were used for one of the teams during the last two games. Cognitive functions were measured before, during and immediately after each football match, as well as core temperature, body mass, plasma osmolality and glucose levels, allowing an estimate of their differential impacts on cognition. The pattern of results suggests that mild-moderate dehydration during exercise in the heat (up to 2.5%) has no clear effect on cognitive function. Instead, plasma glucose and core temperature changes appear to be the main determinants: higher glucose was related to faster and less accurate performance, whereas core temperature rises had the opposite effect. The 50% correlation between plasma glucose and core temperatures observed during exercise in the heat may help to stabilize cognitive performance via their opposing effects. The glucose-like effects of sports drinks appear to be mediated by increased plasma glucose levels, because drinks effects became non-significant when plasma glucose levels were added to the models. The cooling intervention had only a beneficial effect on complex visuo-motor speed.